High-smoothness fluoride-free antifouling coating material for touch screen as well as preparation method and coating of high-smoothness fluoride-free antifouling coating material

By developing fluorine-free antifouling coating materials, using reactive silicone oil, silane coupling agent and hexamethyldisiloxane to form fluorine-free antifouling main agent, the existing PFAS-containing antifouling coating materials are solved in the environment and The accumulated problems in human health have achieved efficient and environmentally friendly coating materials preparation, with excellent durability and anti-fouling properties.

CN119463697APending Publication Date: 2025-02-18深圳怡诚新材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411590962.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The anti-fouling coating materials of existing touch screens contain PFAS compounds, which leads to their accumulation in the environment and human health. Europe and the United States have begun to restrict their use, and there is a problem that they cannot continue to use.

Method used

Develop a fluorine-free antifouling coating material, and prepare a fluorine-free antifouling main agent by using reactive silicone oil, silane coupling agent and hexamethyldisiloxane, combined with leveling agent and solvent to prepare a low-quality antifouling main agent. Coating with good dynamic friction coefficient, excellent smooth touch, durability and stain resistance.

Benefits of technology

It realizes efficient preparation of fluorine-free anti-fouling coating materials. The material is completely free of fluorine elements and meets environmental protection requirements. The coating has excellent durability and anti-fouling properties, as well as low dynamic friction coefficient and excellent smooth touch.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125580180000031
    Figure BDA0005125580180000031
  • Figure BDA0005125580180000041
    Figure BDA0005125580180000041
  • Figure BDA0005125580180000051
    Figure BDA0005125580180000051
Patent Text Reader

Abstract

The invention discloses a high-smoothness fluoride-free antifouling coating material for a touch screen. The high-smoothness fluoride-free antifouling coating material comprises the following components in percentage by weight: 0.2-2% of a fluoride-free antifouling main agent, 0.01-0.04% of a flatting agent and the balance of a solvent, the fluoride-free antifouling main agent is composed of reactive silicone oil, a silane coupling agent and hexamethyldisiloxane; the reactive silicone oil and silane coupling agent accounts for 20% of the fluoride-free antifouling main agent; the reactive silicone oil is polydimethylsiloxane obtained by carrying out single-end or double-end modification on a methoxy group or an ethyoxyl group; the silane coupling agent is one or more of decyl trimethoxy silane and the like. The preparation method comprises the following steps: adding reactive silicone oil and a silane coupling agent into hexamethyldisiloxane to obtain a main agent A; adding the flatting agent into the solvent according to a mass ratio to obtain a solution B; the main agent A is added into the solution B to obtain an antifouling coating, and the antifouling coating is coated on touch screen glass through spray coating, dip coating, blade coating, roll coating and the like to obtain a fluoride-free antifouling coating which is low in dynamic friction coefficient, excellent in smooth touch feeling, good in durability and antifouling property and high in transparency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surface coatings for touch screens, and in particular to a formula of a highly smooth fluorine-free antifouling coating for a touch screen, a preparation method thereof, and a coating. Background Art

[0002] Glass is widely used in many fields such as architecture, ships, kitchen and bathroom, home appliances, car displays, consumer electronics, etc. It is easy to get dirty during use, affecting the appearance and visual experience. Especially in the touch-screen fields such as mobile phones, tablets, e-books, advertising machines, medical industrial control, educational all-in-one machines, and car displays, since the screen is often touched by hand, it is necessary to treat the screen surface with an anti-fouling coating to improve its surface hydrophobicity, oleophobicity, easy cleaning, and smoothness.

[0003] The main film-forming agent material of the anti-fouling coating on the market is alkoxy-modified perfluoropolyether material, such as Daikin's UD509, Shin-Etsu's KY1950 and other products. Then, hydrofluoroether and fluorocarbon solvents are used to dilute the material to a certain proportion before coating to form a film.

[0004] PFAS, or per- and polyfluoroalkyl substances, refers to any substance containing at least one perfluorinated methyl (CF3-) or methylene (-CF2-) carbon atom (without any H / Cl / Br / I). It is a large class of synthetic chemicals that covers more than 10,000 fluorine-containing compounds. The main agents and diluent components of fluorine-containing anti-fouling coating materials on the market basically fall into the category of PFAS compounds.

[0005] Because PFAS compounds decompose abnormally slowly, they tend to accumulate in humans, animals, and the environment over time, including in food, drinking water, soil, and air. Due to this characteristic, PFAS substances are often referred to as "forever chemicals." PFAS exposure poses a significant risk to human health and the environment, and Europe and the United States have begun to restrict the use of PFAS compounds. Currently, the fluorine-containing anti-fingerprint coating materials on the market cannot be used any longer.

[0006] Therefore, it is very necessary to develop fluorine-free antifouling coating materials to replace the currently used fluorine-containing antifouling coating materials. Summary of the invention

[0007] The technical problem to be solved by the present application is to provide a formula of a fluorine-free antifouling coating for a touch screen, which has a low dynamic friction coefficient, excellent smooth touch, good durability and antifouling properties, and high transparency, as well as a preparation method and a coating.

[0008] To solve the above technical problems, the present invention provides a highly smooth fluorine-free antifouling coating material for a touch screen, characterized in that it is made of the following components in weight percentage: 0.2-2% of a fluorine-free antifouling main agent, 0.01-0.04% of a leveling agent, and the balance being a solvent;

[0009] The fluorine-free antifouling main agent is composed of reactive silicone oil, silane coupling agent and hexamethyldisiloxane; the reactive silicone oil plus silane coupling agent accounts for 20% of the total mass of the fluorine-free antifouling main agent, and the mass ratio of reactive silicone oil: silane coupling agent is 9:1 to 1:9; the reactive silicone oil is a polydimethylsiloxane modified with methoxy or ethoxy at one end or both ends, and its molecular weight is 500 to 30000;

[0010] The silane coupling agent is one or more of decyltrimethoxysilane, decyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane and octadecyltriethoxysilane.

[0011] As a preferred solution, the leveling agent is TEGO410.

[0012] The solvent is one or more of butyl acetate, propylene glycol monomethyl ether acetate, and petroleum ether.

[0013] The viscosity of the polydimethylsiloxane is 50-2000 mPa.s.

[0014] At the same time, the present invention also provides a method for preparing the highly smooth fluorine-free antifouling coating material for a touch screen by using the above components and proportions, characterized in that it comprises the following steps:

[0015] S1: Raw material preparation: prepare reactive silicone oil, silane coupling agent, hexamethyldisiloxane, leveling agent and solvent;

[0016] S2: Preparation of fluorine-free main agent: according to the mass ratio, add reactive silicone oil and silane coupling agent to hexamethyldisiloxane in sequence, and shake to make it dispersed evenly to obtain fluorine-free main agent A;

[0017] S3: Add the leveling agent into the solvent according to the mass ratio, stir evenly, and obtain solution B;

[0018] S4: Add the fluorine-free main agent A into the solution B, stir evenly, and obtain the fluorine-free antifouling coating material.

[0019] In addition, the present invention also provides a coating obtained by using the antifouling coating material obtained by the above-mentioned material and preparation method, characterized in that: the antifouling coating material is applied on the touch screen glass by spraying, dipping, scraping, rolling and other coating processes to obtain a highly smooth fluorine-free anti-fingerprint coating.

[0020] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0021] In the technical solution provided by the present invention, compared with the existing perfluoropolyether siloxane antifouling coating material system, the material does not contain fluorine element at all and is not a PFAS-controlled substance.

[0022] According to the experimental results, the film layer has a low dynamic friction coefficient and excellent smooth touch. This is mainly because the molecular chain of polydimethylsiloxane is very long, the molecular weight is large, and the molecules can rotate freely, so polydimethylsiloxane has great flexibility; the silicon-oxygen bond has a large bond energy and a long bond length, which makes the intermolecular force of polydimethylsiloxane weak, so the molecules can move and rotate relatively easily, enhancing flexibility; the surface energy of polydimethylsiloxane is 21-22mN / m, and the lower surface energy can reduce the friction resistance during touch.

[0023] After coating, it can form a chemical bond with the substrate, and the film has excellent durability and antifouling properties. After the coating material is coated, the reactive polydimethylsiloxane and the methoxy or ethoxy at the end of the silane coupling agent in the material can undergo a hydrolysis reaction with water in the air to produce silanol, and further undergo a dehydration condensation reaction with the hydroxyl group on the surface of the substrate, and finally form a strong silicon-oxygen bond with the surface of the substrate, thereby improving the bonding ability between the coating and the substrate; at the same time, a cross-linking reaction also occurs between the polydimethylsiloxane and the active groups of the silane coupling agent, so that a dense network structure is produced at the bottom of the molecular chain, making the coating have excellent durability, and the lower surface energy of the coating makes it have excellent anti-fouling and easy-to-wipe effects. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with the embodiments.

[0025] In each embodiment of the present invention, all components are commercially available products. The trimethoxy double-end-capped silicone oil and leveling agent are manufactured by the manufacturer shown in Table 1, and the remaining components can be commercially available general products. The components and quality of each embodiment are shown in Table 1.

[0026] Table 1

[0027]

[0028]

[0029] Example 1

[0030] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is prepared from the following components by weight: 0.036 g of trimethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.004 g of octadecyltrimethoxysilane is used as a silane coupling agent, 0.16 g of hexamethyldisiloxane, 0.01 g of TEGO410 leveling agent is used as a solvent, and 99.79 g of propylene glycol monomethyl ether acetate is used as a solvent.

[0031] Preparation method of the above-mentioned highly smooth fluorine-free antifouling coating material:

[0032] S1: Raw material preparation: prepare the components according to the above mass grams;

[0033] S2: Preparation of fluorine-free antifouling main agent: according to the mass ratio, add reactive silicone oil and silane coupling agent to hexamethyldisiloxane in sequence, and shake to make it dispersed evenly, to obtain fluorine-free antifouling main agent A, wherein the mass of reactive silicone oil plus silane coupling agent accounts for 20% of the total mass of fluorine-free main agent;

[0034] S3: Add all the leveling agent TEGO410 into the solvent propylene glycol monomethyl ether acetate, stir evenly, and obtain solution B;

[0035] S4: Add the fluorine-free antifouling main agent A into solution B and stir evenly to obtain a highly smooth fluorine-free antifouling coating.

[0036] When in use, the glass substrate is first cleaned by ultrasonic or flat cleaning machine and plasma treated, and then the prepared high-slip fluorine-free antifouling coating is sprayed on the surface of the glass substrate by spraying, with a spraying amount of 45g / ㎡, an atomization pressure of 30-40Psi, a nozzle height of 30-40mm, and baked at 150℃ for 30min after spraying.

[0037] The baked glass substrate was cooled to room temperature and allowed to stand for 2 h before being tested for dynamic friction coefficient (COF), water contact angle, diiodomethane contact angle, edible oil contact angle (commercially available corn oil), dust-free cloth wear resistance, and oily pen line drawing tests.

[0038] Dynamic friction coefficient (COF) test conditions: the test instrument is FPT-F1 friction coefficient tester, the test medium is oil-absorbing paper, the slider area is 20×20mm, the slider mass is 200g, and the test rate is 150mm / min.

[0039] Contact angle test: drop volume 2 μl

[0040] Dust-free cloth wear test: Wrap the friction head with 4 layers of dust-free cloth, the friction head area is 10×10mm, the load is 1Kg, the stroke is 40mm, the wear rate is 60Cycles / min, and the water contact angle is tested after wearing for 10000Cycles.

[0041] Oil pen line test:

[0042] Use a Hi-Mckee (ZEBRA) oil pen to draw a line on the coating sample, and then carefully observe the changes in the ink trace. E: The ink fades quickly

[0043] G: Ink fades

[0044] F: Part of the ink fades away

[0045] NG: The ink is not repellent. The above test results are shown in Table 2.

[0046] Table 2

[0047]

[0048] Example 2

[0049] The highly smooth fluorine-free antifouling coating material provided in Example 2 is shown in Table 1, and each 100 g is composed of the following weight array components: 0.07 g of trimethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.03 g of hexadecyltrimethoxysilane is used as silane coupling agent, 0.4 g of hexamethyldisiloxane, 0.02 g of TEGO410 leveling agent is used as solvent, and 99.48 g of propylene glycol monomethyl ether acetate is used as solvent.

[0050] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0051] Example 3

[0052] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.1 g of trimethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.1 g of dodecyltrimethoxysilane is used as silane coupling agent, 0.8 g of hexamethyldisiloxane, 0.04 g of TEGO410 leveling agent is used as solvent, and 98.96 g of propylene glycol monomethyl ether acetate is used as solvent.

[0053] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0054] Example 4

[0055] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.09 g of trimethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.21 g of decyltrimethoxysilane is used as silane coupling agent, 1.2 g of hexamethyldisiloxane, 0.02 g of TEGO410 leveling agent is used as silane coupling agent, and 98.48 g of mixed solvent (petroleum ether: propylene glycol monomethyl ether acetate = 1:1) is used as solvent.

[0056] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0057] Example 5

[0058] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.04 g of trimethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.36 g of dodecyltrimethoxysilane is used as silane coupling agent, 1.6 g of hexamethyldisiloxane, 0.02 g of TEGO410 leveling agent is used as silane coupling agent, and 97.98 g of mixed solvent (petroleum ether: butyl acetate = 1:1) is used as solvent.

[0059] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0060] Example 6

[0061] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight array components: 0.06 g of trimethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.06 g of octadecyltrimethoxysilane is used as silane coupling agent, 0.48 g of hexamethyldisiloxane, 0.01 g of TEGO410 leveling agent is used, and 99.39 g of propylene glycol monomethyl ether acetate is used as solvent.

[0062] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0063] Example 7

[0064] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.072 g of trimethoxy single-end blocked silicone oil is used as reactive silicone oil, 0.048 g of hexadecyltrimethoxysilane is used as silane coupling agent, 0.48 g of hexamethyldisiloxane, 0.01 g of TEGO410 leveling agent is used as solvent, and 99.39 g of propylene glycol monomethyl ether acetate is used as solvent.

[0065] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0066] Example 8

[0067] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.06 g of triethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.06 g of decyltrimethoxysilane is used as silane coupling agent, 0.48 g of hexamethyldisiloxane, 0.02 g of TEGO410 leveling agent is used as solvent, and 99.38 g of petroleum ether is used as solvent.

[0068] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0069] Example 9

[0070] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.048 g of triethoxy double-end-capped silicone oil is used as reactive silicone oil, 0.072 g of dodecylethoxysilane is used as silane coupling agent, 0.48 g of hexamethyldisiloxane, 0.03 g of TEGO410 leveling agent is used as solvent, and 99.37 g of butyl acetate is used as solvent.

[0071] Example 10

[0072] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.08 g of triethoxy single-end blocked silicone oil is used as reactive silicone oil, 0.08 g of hexadecyltrimethoxysilane is used as silane coupling agent, 0.64 g of hexamethyldisiloxane, 0.02 g of TEGO410 leveling agent is used as silane coupling agent, and 99.18 g of mixed solvent (petroleum ether: propylene glycol monomethyl ether acetate = 1:1) is used as solvent.

[0073] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0074] Embodiment 11

[0075] The present invention provides a highly smooth fluorine-free antifouling coating material, as shown in Table 1, wherein each 100 g is composed of the following weight matrix components: 0.07 g of triethoxy single-end blocked silicone oil is used as reactive silicone oil, 0.07 g of dodecylethoxysilane is used as silane coupling agent, 0.56 g of hexamethyldisiloxane, 0.02 g of TEGO410 leveling agent is used as silane coupling agent, and 99.28 g of mixed solvent (petroleum ether:butyl acetate=1:1) is used as solvent.

[0076] The preparation steps, usage methods and experimental tests are the same as those in Example 1.

[0077] In the above-mentioned embodiments 1 to 11, only a part of the substances are listed. The remaining substances or combinations given in the content of the invention and the substances in the embodiments can achieve the purpose of the invention in terms of function and technical effect, and are not listed one by one here.

Claims

1. A highly smooth fluorine-free antifouling coating material for a touch screen, characterized in that: The invention is made of the following components in weight percentage: 0.2-2% of fluorine-free antifouling main agent, 0.01-0.04% of leveling agent, and the balance of solvent; The fluorine-free antifouling main agent is composed of reactive silicone oil, silane coupling agent and hexamethyldisiloxane; the reactive silicone oil plus silane coupling agent accounts for 20% of the total mass of the fluorine-free antifouling main agent, and the mass ratio of reactive silicone oil: silane coupling agent is 9:1 to 1:9; the reactive silicone oil is a polydimethylsiloxane modified with methoxy or ethoxy at one end or both ends, and its molecular weight is 500 to 30000; The silane coupling agent is one or more of decyltrimethoxysilane, decyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane and octadecyltriethoxysilane.

2. The highly smooth fluorine-free antifouling coating material for touch screen according to claim 1, characterized in that: The leveling agent is TEGO410.

3. The highly smooth fluorine-free antifouling coating material for touch screen according to claim 1, characterized in that: The solvent is one or more of butyl acetate, propylene glycol monomethyl ether acetate, and petroleum ether.

4. The highly smooth fluorine-free antifouling coating material for a touch screen according to claim 1, characterized in that: The viscosity of the polydimethylsiloxane is 50-2000 mPa.s.

5. The method for preparing the highly smooth fluorine-free antifouling coating material for touch screens according to any one of claims 1 to 4, characterized in that: The steps include: S1: Raw material preparation: prepare reactive silicone oil, silane coupling agent, hexamethyldisiloxane, leveling agent and solvent; S2: Preparation of fluorine-free main agent: according to the mass ratio, add reactive silicone oil and silane coupling agent to hexamethyldisiloxane in sequence, and shake to make it dispersed evenly to obtain fluorine-free main agent A; S3: Add the leveling agent into the solvent according to the mass ratio, stir evenly, and obtain solution B; S4: Add the fluorine-free main agent A into the solution B, stir evenly, and obtain the fluorine-free antifouling coating material.

6. The coating obtained by using the antifouling coating material obtained by the preparation method of the highly smooth fluorine-free antifouling coating material for touch screens according to claim 5 is characterized in that: The antifouling coating material is applied on the touch screen glass through spraying, dipping, scraping, rolling and other coating processes to obtain a highly smooth fluorine-free anti-fingerprint coating.

Citation Information

Patent Citations

  • Preparation method for static amphiphilic dynamic hydrophobic-oileophobic fluorine-free transparent coating

    CN109181538A